A SEMANTIC ANALYSIS OF SPEECH ACTION AND LEXICAL CHOICHES IN COSTUMER SERVICE APOLOGY AND COMPLAINT IN TELKOMSEL RESPONSES - Elina Rosa Sihotang; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the public service sector, issuing an apology is essential. Customer service representatives, particularly in public services, are typically tasked with handling client complaints. Therefore, public service institutions require effective apology strategies to address these concerns appropriately. This study aims to explore the most commonly used apology strategies by Telkomsel's customer service personnel. The research focuses on identifying which types of apology approaches are more frequently used in everyday interactions. This study may also contribute to a broader understanding of how public services utilize apology strategies. A qualitative research approach is applied in this investigation. The analysis is based on Trosborg’s (1995) framework of apology strategies. Findings indicate that Telkomsel customer service representatives predominantly use explanations or accounts in 50% of the cases when dealing with customer complaints. This approach is often employed to calm customers and ease emotional tension.